2012
DOI: 10.1099/vir.0.045518-0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel Torque teno sus virus species: genetic characterization, epidemiological assessment and disease association

Abstract: The study describes a novel Torque teno sus virus (TTSuV) species, provisionally named Torque teno sus virus k2b (TTSuVk2b), originally found in commercial pig sera by applying the rollingcircle amplification technique. Full-length sequences of TTSuVk2b were obtained, annotated and used in the phylogenetic analyses, which revealed that TTSuVk2b is a novel Anellovirus species within the genus Kappatorquevirus of the family Anelloviridae. Quantitative PCR techniques were developed to determine total TTSuV DNA qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…The strongest connection between TTSuV and disease is as a cofactor in PCV-2-associated syndromes. 6 PCV-2 and TTSuV have been previously identified together in association with PMWS. 34 Interestingly, TTSuV was found in most serum samples, including all 6 PCVAD pigs, and was found in the tonsils of 3 pigs removed at 32 dpi because of morbidity associated with PCVAD.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest connection between TTSuV and disease is as a cofactor in PCV-2-associated syndromes. 6 PCV-2 and TTSuV have been previously identified together in association with PMWS. 34 Interestingly, TTSuV was found in most serum samples, including all 6 PCVAD pigs, and was found in the tonsils of 3 pigs removed at 32 dpi because of morbidity associated with PCVAD.…”
Section: Discussionmentioning
confidence: 99%
“…Data related to infection with TTSuVk2b, the most recently identified species, are still limited. A study on 244 pig serum samples from 17 different countries reported an overall 40% prevalence of infection [36], whereas Blois et al reported an 11.5% prevalence of TTSuVk2b in 721 Italian pigs [70]. The high prevalence of TTSuV in the swine population indicates the existence of effective mechanisms of transmission.…”
Section: Animal Ttvsmentioning
confidence: 99%
“…In addition to TTV, in humans there are two other TTV-like species: TTMV and TTMDV, classified within the family Anelloviridae and belonging to the genera Betatorquevirus and Gammatorquevirus, respectively. TTVs infecting pigs (Sus domesticus) include four species described so far: Torque teno sus virus 1a and 1b (TTSuV1a and TTSuV1b), belonging to the genus Iotatorquevirus, and Torque teno sus virus k2a and k2b (TTSuVk2a and TTSuVk2b), the latter being the most recently discovered species, belonging to the genus Kappatorquevirus [36].…”
Section: Discovery and Characterization Of Ttvmentioning
confidence: 99%
“…Although it seems that TTSuV infection is not directly responsible for any disease, the possibility remains that they play a role in different co-infections (Cornelissen-Keijsers et al, 2012;Taira et al, 2009). …”
mentioning
confidence: 99%
“…Viral prevalence increases with age and in most animals the infection can be persistent (Sibila et al, 2009a, b;Taira et al, 2009). New porcine TT virus species (named TTSuV1a and TTSuV1b) have been proposed based on new sequence data (Cornelissen-Keijsers et al, 2012).…”
mentioning
confidence: 99%